2021
DOI: 10.3390/ma14227073
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ball Burnishing on Dry Fretting

Abstract: Experiments were conducted under a dry gross fretting regime. Steel discs were put in contact with ceramic balls. Before tribological tests, discs were subjected to ball burnishing with different pressures. Due to ball burnishing, a decrease in surface amplitude and an increase in microhardness occurred. Ball burnishing caused decreases in the friction force and volumetric wear of up to 45% in comparison to sliding pairs containing milled discs. The friction force and volumetric wear were higher for a higher r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…The roughness results determine that the number of passes is the most influential parameter and is followed by the burnishing force, which coincides with some bibliographic references with the same material [21]. It has also been proven that VABB offers better results than BB in terms of surface quality, as was also expected [41,42].…”
Section: Discussionsupporting
confidence: 82%
“…The roughness results determine that the number of passes is the most influential parameter and is followed by the burnishing force, which coincides with some bibliographic references with the same material [21]. It has also been proven that VABB offers better results than BB in terms of surface quality, as was also expected [41,42].…”
Section: Discussionsupporting
confidence: 82%
“…It is also confirmed that the performance properties depend more on the topography of the surface than on the numerical value of the roughness parameter, and so for their evaluation, it is advisable to use special parameters [26] and the Abbott-Firestone diagram [27,28]-especially for surfaces with formed surface structures. It is also confirmed that for finishing operations, it is advisable to use ball-rolling operations, which reduce the surface roughness and improve its physical and mechanical quality parameters [29,30].…”
Section: Discussion Of Research Findingsmentioning
confidence: 73%
“…The Ra, R mrk2 , and R vk criteria were included only for reference. The specimens with RMRs were created using ball-burnishing operations conducted on a HAAS (Philadelphia, PA, USA) TM-1 CNC milling machine through a specially designed ball-burnishing tool that does not use forced vibrations [16,17]. After the RMRs were created, the specimens, which have dimensions of 30 × 40 × 4 mm were cut-off from the raw material sheet using a fiber laser cutter machine GN NCF 3015.…”
Section: Materials Experimental Design and Equipment For Preparing Th...mentioning
confidence: 99%
“…RMRs formed on the operational surface of friction pair parts could extend its life by easily providing the required conditions to reach liquid friction sliding, a greater lubrication capacity of the friction surfaces, and a shorter duration of the run-in period; lower friction coefficients in the friction pair, and consequently, a higher wear resistance have been detailed in Swirad et al [17].…”
Section: Introductionmentioning
confidence: 99%